2022
DOI: 10.20956/hajas.v4i2.20995
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Efficiency of Cows in Different Parity

Abstract: Livestock is one of the agricultural sectors that plays an important role in providing animal products. Cows are one of the largest meat and dairy producers. The low reproductive efficiency of cattle is the biggest problem in terms of its development. Increasing reproductive efficiency through artificial insemination programs is one way to enhance livestock populations. Reproductive efficiency parameters can be measured through values of Service per Conception (S/C) and Conception Rate (CR). Service per concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
0
0
1
Order By: Relevance
“…The AI rate is considered good at 1.6 times, 1.6-1.8 times is average, around two times is acceptable, while three or more AI times per pregnancy is considered a bad indicator [34]. It is known that the number of inseminations per pregnancy and the number of days from calving to the first AI increases with the age of the animals [35]. Therefore, in our study, the AI rate after an abortion was found to be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…The AI rate is considered good at 1.6 times, 1.6-1.8 times is average, around two times is acceptable, while three or more AI times per pregnancy is considered a bad indicator [34]. It is known that the number of inseminations per pregnancy and the number of days from calving to the first AI increases with the age of the animals [35]. Therefore, in our study, the AI rate after an abortion was found to be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Par labu MA reižu skaitu uz grūsnību tiek uzskatīts 1,6 reizes, par vidēju 1,6 -1,8 reizes, par akceptējamu ap 2 reizēm, bet 3 un vairāk MA reižu skaits uz grūsnību tiek uzskatīts par sliktu rādītāju (Siatka et al, 2017). Zināms, ka apsēklošanas reižu skaits uz grūsnību, tāpat kā dienu skaits no atnešanās līdz pirmajai MA palielinās līdz ar dzīvnieku vecumu (Mutmainna et al, 2022).…”
Section: Att Coxiella Burnetii Imūnatbildes Serumā Klātbūtnes Pienā U...unclassified